ANALISIS REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH TAHUN 2017 PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KUTAI KARTANEGARA - Melinda, - Melinda (EKONOMIA, 2019)
This study aims to compile a Budget Realization Report (LRA) in which there are ratios with criteria. The heory used in this research is government accounting standards and the hypothesis stated is that the APBD income variance is not good, very low regional independence, the effectiveness of PAD is very ineffective, the variance of APBD spending is not profitable. The analytical tool in this study uses descriptive and quantitative methods that is by studying government accounting standards applied in the field so that there are differences with the phenomena and fields in the Regional Financial and Asset Management Agency (BPKAD) of Kutai Kartanegara.Based on the results of the study, then it can be concluded that regionl revenue has not been able to obtain income exceeding the arnount budgeted and has not been able to incrcase the regional original revenue including its resourees. Whereas regional xpenditures for operating expenditure and capital expenditure on total regional expenditures have not been fully able to increase harmony with total regional expenditure